External exposome and all-cause mortality in European cohorts: the EXPANSE project - Nobile, Federica; Dimakopoulou, Konstantina; Åström, Christofer; Coloma, Fabián; Dadvand, Payam; de Bont, Jeroen; de Hoogh, Kees; Ibi, Dorina; Katsouyanni, Klea; Ljungman, Petter; Melén, Erik; Nieuwenhuijsen, Mark; et al. (Frontiers in Epidemiology, 2024)
Background: Many studies reported associations between long-term exposure to environmental factors and mortality; however, little is known on the combined effects of these factors and health. We aimed to evaluate the association between external exposome and all-cause mortality in large administrative and traditional adult cohorts in Europe. Methods: Data from six administrative cohorts (Catalonia, Greece, Rome, Sweden, Switzerland and the Netherlands, totaling 27,913,545 subjects) and three traditional adult cohorts (CEANS-Sweden, EPIC-NL-the Netherlands, KORA-Germany, totaling 57,653 participants) were included. Multiple exposures were assigned at the residential addresses, and were divided into three a-priori defined domains: 1) air pollution [fine particulate matter (PM2.5), nitrogen dioxide (NO₂), black carbon (BC) and warm-season Ozone (warm-O3)]; 2) land/built environment (Normalized Difference Vegetation Index -NDVI, impervious surfaces, and distance to water); 3) air temperature (cold-and warm-season mean and standard deviation). Each domain was synthesized through Principal Component Analysis (PCA), with the aim of explaining at least 80% of its variability. Cox proportional-hazards regression models were applied and the total risk of the external exposome was estimated through the Cumulative Risk Index (CRI). The estimates were adjusted for individual-and area-level covariates. Results: More than 205 million person-years at risk and more than 3.2 million deaths were analyzed. In single-component models, IQR increases of the first principal component of the air pollution domain were associated with higher mortality [HRs ranging from 1.011 (95% CI: 1.005-1.018) for the Rome cohort to 1.076 (1.071-1.081) for the Swedish cohort]. In contrast, lower levels of the first principal component of the land/built environment domain, pointing to reduced vegetation and higher percentage of impervious surfaces, were associated with higher risks. Finally, the CRI of external exposome increased mortality for almost all cohorts. The associations found in the traditional adult cohorts were generally consistent with the results from the administrative ones, albeit without reaching statistical significance. Discussion: Various components of the external exposome, analyzed individually or in combination, were associated with increased mortality across European cohorts. This sets the stage for future research on the connections between various exposure patterns and human health, aiding in the planning of healthier cities.